1965
DOI: 10.1017/s0003356100022273
|View full text |Cite
|
Sign up to set email alerts
|

The nutrition of the early-weaned calf VIII. The effect on nitrogen retention of diets containing different levels of fish meal

Abstract: SUMMARY1. All-concentrate diets containing four different levels of Peruvian (anchovy) fish meal and varying in crude protein content from 14·8% to 21·7% in dry matter were given ad libitum to 8 early-weaned Friesian calves over a live-weight range of 60–100 kg.2. Nitrogen retention was significantly higher on diets containing 21·7% and 19·4% crude protein in dry matter than on diets with 16·8% and 14·8% crude protein. Nitrogen retention as a percentage of dietary intake appeared to be less on the diet with 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1966
1966
1988
1988

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Preston, Whitelaw, MacLeod and Philip (1965) suggested that for calves weaned at approximately 4 weeks of age, and receiving an all-concentrate diet, a level of 17-19% crude protein in the dry matter, supplying 270-340 g. digestible crude protein per day, was required. live-weight gaining at 0*50 kg.…”
Section: Rowett Research Institute Bucksbum Aberdeenmentioning
confidence: 99%
“…Preston, Whitelaw, MacLeod and Philip (1965) suggested that for calves weaned at approximately 4 weeks of age, and receiving an all-concentrate diet, a level of 17-19% crude protein in the dry matter, supplying 270-340 g. digestible crude protein per day, was required. live-weight gaining at 0*50 kg.…”
Section: Rowett Research Institute Bucksbum Aberdeenmentioning
confidence: 99%
“…It follows, therefore, that the mean values for digestible protein intake of these calves represent the minimum protein requirements for the live-weights and live-weight gains observed. The value of 240 g./day is also below the allowance suggested by Preston, Whitelaw, MacLeod and Philip (1965) of between 267 and 342 g. digestible protein/day for Friesian calves of 82 kg. live-weight gaining at 0-91 kg./day, the minimum digestible protein requirement will be 240 g./day, and for a calf of 78-6 kg.…”
Section: Discussionmentioning
confidence: 54%
“…on diets varying in digestibility. A considerable amount of information has been obtained recently on the nitrogen metabolism of young calves fed on all-concentrate diets (see Preston, Whitelaw, MacLeod andBowers, Preston, McDonald, MacLeod and but there is less information of a similar nature for lambs fed on such diets. The following experiment was carried out to assess the intake of energy and utilisation of dietary nitrogen by lambs fed ad libitum on three simple all-concentrate diets during the latter stages of fattening.…”
Section: A Note On Energy Intake and Nitrogen Balance Of Fattening Lamentioning
confidence: 99%